The antigenic link between thyroid autoimmunity and breast cancer. (August 2020) - Muller, Ilaria; Barrett-Lee, Peter J.
Abstract: The association between breast cancer and benign thyroid disorders, in particular thyroid autoimmunity, has been debated for decades. Autoantibodies to thyroid peroxidase, the hallmark of thyroid autoimmunity, have a higher prevalence among patients with breast cancer compared with the general population. Furthermore a correlation between their positivity and a better prognosis of breast cancer was found in several independent small-scale studies, even if such observation was not confirmed in a subsequent retrospective study conducted on the largest patient cohort to date. The thyroid and mammary glands present several biological similarities, therefore the hypothesis of an immune response to shared thyroid/breast antigens could in part explain the association between thyroid autoimmunity and breast cancer. The sodium iodide symporter is expressed in both glands, however it seems unlikely to be the key common antigen, considering that autoantibodies targeting it are rare. Instead thyroid peroxidase, one of the major thyroid autoantigens, is also expressed in breast tissue and therefore represents the main antigenic link between thyroid autoimmunity and breast cancer. Furthermore lactoperoxidase, an enzyme of the same family that shares structural similarities with thyroid peroxidase, is expressed in neoplastic breast cells and is responsible for the cross-reactivity with some autoantibodies to thyroid peroxidase. Novel strategies for the diagnosis and treatment of breast cancer might take advantage of the antigenic link between thyroid and breast tissues.